Desain Formulir Pengkajian Awal Neonatus di Rumah Sakit Tingkat III Baladhika Husada Jember - Rizky Farah Dilla; Dony Setiawan Hendyca Putra (Politeknik Negeri Jember, 2020)
The neonatal preliminary assessment form is one of the important forms, because it includes informationabout newborns. Baladhika Husada Hospital in Jember is one of the hospitals which still does not have apreliminary assessment form specifically for newborns or neonates, there still uses initial assessment formsfor general patients. The purpose of this study was to design a neonatal initial assessment form at BaladhikaHusada Hospital Level III Jember. This type of research is a qualitative study with research subjects includingSp.A doctors, midwives, nurses, chief medical records, and medical records officers. Data collectiontechniques in this study used interviews, observation, brainstorming. The results of this study were seen fromthe physical aspects of the neonatal initial assessment form using white paper with a size of 70 grams F4 (33cm and 21.5 cm) in portrait form. Viewed from the anatomical aspects of the neonatal heading assessmentform, the logo, the name of the agency, the address of the agency, and the title of the form, for theintroduction, are represented by the title. Viewed from the aspect of the contents of the neonatal preliminaryassessment form, the data added consisted of obstetric status, anthropometric vital signs, apgar scoreassessment, and physical examination starting from B1 - B7. Suggestions from researchers on the results ofthe neonatal initial assessment form design are expected to be implemented at Baladhika Husada HospitalLevel III Jember.